Suitability of Almond Bagasse Powder as a Wheat Flour Substitute in Biscuit Formulation - S. Duarte; J. Harasym; J. Sánchez-García; M. Kelaidi; E. Betoret; N. Betoret (Journal of Food Quality)
Almond bagasse, a by-product derived from the production of almond vegetable drink, contains antioxidants, fibre, protein, and a high-fat content, presenting itself as a potential functional ingredient for the food industry. This study aimed to assess the powder derived from almond bagasse as a suitable alternative in the formulation of bakery goods. Various formulations substituting wheat flour with almond bagasse powder, obtained by air drying or freeze-drying at 10%, 15%, and 25%, were analysed in terms of technological and rheological properties. Furthermore, the physical and antioxidant attributes of biscuits with superior nutritional and functional values produced using these blends were examined. The results revealed significant changes in oil retention capacity, stability, and emulsifying activity, influenced by both the level of wheat flour replacement and the drying method used to obtain the almond bagasse powder. The most significant changes were observed in the emulsifying activity, which was zero in the wheat flour and showed values of 20% in the hot air-dried almond bagasse powder and 59% in that obtained by freeze-drying. In the blends, the values of this variable ranged from 1.8% to 7.1%. The highest value was obtained with a 25% replacement of wheat flour by freeze-dried almond powder. On the other hand, the lack of starch and the high concentration of fat (around 25%) and insoluble fibre (higher than 20%) in the almond bagasse powder determined the viscoelastic behaviour of the hydrated blends. As the percentage of substitution with the almond bagasse powder increased, the final viscosity decreased, being reduced from 2302 MPa·s in the wheat flour to 873 MPa·s in the blend containing 25% hot air-dried almond powder. It is worth noting that, the use of these blends for biscuit preparation resulted in a final product with a higher content of antioxidant components. The highest increase in antiradical capacity was 33% and was observed in the biscuits obtained with the mixture containing 25% hot air-dried almond powder.